Energy for water utilization in China and policy implications for integrated planning. Issue 3 (3rd May 2016) - Li, Xi; Liu, Jie; Zheng, Chunmiao; Han, Guoyi; Hoff, Holger
Abstract: Significant energy resources are needed for traditional and nontraditional water utilization in China. Yet the interlinkages between water and energy have not received adequate attention in the country. To address this gap, this article disaggregates and quantifies the magnitude and direction of energy and water flows in China at the national level through Sankey diagrams. Spatial distributions of energy use by different components of the water supply were further mapped at the provincial level to discern regional differences. The results of this study show that the total energy consumption by water abstraction, treatment and distribution, as well as waste treatment and reuse, amounts to 193.5 TWh of electricity, or about 4% of the total national electricity usage. The outcome of this study offers important policy implications for integrated water and energy planning and management and will contribute to achieving the goal of low-energy water utilization in the future.